2014
DOI: 10.1007/s00330-014-3316-5
|View full text |Cite
|
Sign up to set email alerts
|

CT volumetry for gastric carcinoma: association with TNM stage

Abstract: CT volumetry of gastric carcinoma is feasible and reproducible. Tumour volume <19.4 ml predicts T1-stage gastric cancer with 91% sensitivity and 100% specificity (P = 0.0001). Tumour volume >95.7 ml predicts metastatic gastric cancer with 87% sensitivity and 78.5% specificity (P = 0.0001). CT volumetry may be a useful adjunct for staging gastric carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
27
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 32 publications
7
27
2
Order By: Relevance
“…CT volumetric parameter has gained acceptance as a prognostic marker for gastric cancer [9] since Kikuchi et al reported the usefulness of CT volumetry to predict patients’ survival as well as predict TNM staging in gastric cancer [10, 11]. In terms of rectal cancer, there have been several reports showing the usefulness of CT or MR volumetry to predict treatment response after chemoradiation therapy [1215].…”
Section: Introductionmentioning
confidence: 99%
“…CT volumetric parameter has gained acceptance as a prognostic marker for gastric cancer [9] since Kikuchi et al reported the usefulness of CT volumetry to predict patients’ survival as well as predict TNM staging in gastric cancer [10, 11]. In terms of rectal cancer, there have been several reports showing the usefulness of CT or MR volumetry to predict treatment response after chemoradiation therapy [1215].…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the serosal defects of color-diffused type GC reflect an invasive tendency of primary tumor that is undetectable in the course of preoperative imaging and other diagnostics. [20][21][22] This explains the observed homogeneity of prognosis across all stages of color-diffused type GC, as detailed herein. Furthermore, such defects may create difficulty in determining an accurate histologic depth of invasion.…”
Section: Discussionmentioning
confidence: 73%
“…Kikuchi et al (18) suggested that staging system based on tumor volume measured from continuous tissue sections by the surface rendering method after surgery may have advantages over conventional staging systems for gastric cancer. Previously published data showed that tumor volume measured by CT is also feasible and reproducible, which could provide useful adjunct information for TNM staging of gastric cancer (13). They demonstrated that CT volumetry correlated well with T and N stages for gastric cancer without preoperative treatment with an AUC of 0.89 for ≥T2 stage and 0.75 for ≥N1 stage.…”
Section: Discussionmentioning
confidence: 98%
“…They suggested that T-staging by CT after neoadjuvant chemotherapy should not be considered in clinical decision-making. More recently, studies reported that tumor volume measurement could provide useful information for preoperative staging (13), assessment of response to neoadjuvant chemotherapy (14), and predicting prognosis of gastric cancer (15). Tumor volume reduction rates were significantly correlated with histopathologic grades of tumor regression in gastric cancer patients with a tumor volume reduction rate of 35.6% or higher (14).…”
mentioning
confidence: 99%